The Theoretical Research for the Rotor/Fuselage Unsteady Aerodynamic Interaction Problem - Liu Dawei; Xin Ji; Huang Jun (Journal of Aerospace Technology and Management, 2016)
Based on coupled unsteady panel/free-wake method, a universal analysis model was established, which provides a good prediction for the rotor/fuselage unsteady aerodynamic interaction. Considering the deficiencies of the traditional time-marching rotor free-wake algorithms, notably on stability and efficiency, the CB3D algorithm with 3rd-order accuracy is proposed. For solving the problem that part of the wake vortices may penetrate the fuselage, a “material line” rectification method with 3rd-order accuracy is proposed. An analysis for the model accuracy was then conducted to validate the accuracy of the new model, and a comparison against the available experimental data is performed. The simulated results show a good agreement with these experimental data. With the new model, several simulations are conducted for the typical rotor/fuselage aerodynamic interaction, and the results are analyzed.